2004
DOI: 10.1017/s0074180900182142
|View full text |Cite
|
Sign up to set email alerts
|

X-rays from M-type Giants—Signs of Late Stellar Activity?

Abstract: Abstract. We present recent X-ray and optical observations of five Mtype giants which were detected as strong X-ray sources. One of these stars, HR 5512, shows short-term variations in both X-ray flux as well as in the shape of the Ho and Ca II H+K lines, and it rotates much faster than M-type giants usually do. No indication of binarity has been found for this star. We propose that the X-ray emission of HR 5512 is related to a large degree of stellar activity. For two other stars (15 Tri, HR 7547) radial velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 6 publications
6
31
0
Order By: Relevance
“…The RV accuracy of NARVAL is 20−30 m s −1 (Moutou et al 2007;Aurière et al 2009 Hünsch et al (2004) and Famaey et al (2009) from measurements with CORAVEL (Udry et al 1997). Famaey et al (2009) included their EK Boo observations in two of their diagnosis plots and concluded that the star "appears amidst the non-binary M giants".…”
Section: Radial Velocity Binarity and Pulsationsmentioning
confidence: 93%
See 3 more Smart Citations
“…The RV accuracy of NARVAL is 20−30 m s −1 (Moutou et al 2007;Aurière et al 2009 Hünsch et al (2004) and Famaey et al (2009) from measurements with CORAVEL (Udry et al 1997). Famaey et al (2009) included their EK Boo observations in two of their diagnosis plots and concluded that the star "appears amidst the non-binary M giants".…”
Section: Radial Velocity Binarity and Pulsationsmentioning
confidence: 93%
“…But in this case, v sin i has been determined. The CORAVEL value obtained on the basis of the cross-correllation method (Melo et al 2001) is 11 ± 1 km s −1 (Hünsch et al 2004). Our NARVAL data and the spectral synthesis method (permitting us to account for rotational and macroturbulent broadening) yield v sin i of 8.5 km s −1 with an accuracy 0.5 km s −1 .…”
Section: Rotationmentioning
confidence: 96%
See 2 more Smart Citations
“…If this is the case for AGB stars, as proposed in the dynamic-magnetic models, then the X-ray luminosity should be a factor of $10 6 10 8 stronger than in the Sun (Soker & Zoabi 2002). Soker & Zoabi (2002) conclude that this expectation, of L X $ 10 31 10 35 ergs s À1 , is in sharp contradiction with most ROSAT observations; these observations demonstrate that the X-ray luminosities of red giant stars typically are only marginally larger than the solar X-ray luminosity (Schröder et al 1998) and that L X likely further decreases in late giant evolution (Hünsch & Schröder 1996). On the other hand, some red giants are known to be relatively luminous in X-rays (i.e., L X $ 10 30 ergs s À1 ; e.g., Hünsch & Schröder 1996;Hünsch 2001).…”
Section: Introductionmentioning
confidence: 94%